The Impact of Health Promotion Using Leaflet Media on Mothers’ Knowledge of the Early Stimulation of Toddlers’ Development and Growth - Shalahuddin I; Salsabila S; Rukmasari EA; Rosidin U; Eriyani T; Pebrianti S; Maulana I (Journal of Multidisciplinary Healthcare)
Iwan Shalahuddin, Shafa Salsabila, Ema Arum Rukmasari, Udin Rosidin, Theresia Eriyani, Sandra Pebrianti, Indra Maulana Faculty of Nursing, Padjadjaran University, Jatinangor, West Java, IndonesiaCorrespondence: Iwan Shalahuddin, Faculty of Nursing, Padjadjaran University, Jl. Raya Bandung Sumedang KM 21, Jatinangor, West Java, 45363, Indonesia, Tel/Fax +62 (022) 7795596, Email shalahuddin@unpad.ac.idIntroduction: Children who get inadequate stimulation will develop slower than those who receive regular and purposeful stimulus. Toddler-age toddlers face a variety of growth and development issues as a result of their mother’s lack of information about stimulating their development.Objective: The purpose of this study is to analyze the impact of health education using leaflet media on mothers’ knowledge of early stimulation for toddler-age kids from Gunung Tua village, Subang Regency.Methods: This study’s research design is a quasi-experiment using a one-group pretest-posttest approach. This study’s population consists of moms with toddler-aged children living in Gunung Tua village, Subang. The study’s sample size is 80 moms, including criteria for inclusion and exclusion. The data collecting method employs a questionnaire derived from the SDIDTK (Stimulation, Detection and Early Intervention of Growth and Development) book Ministry of Health, which contains 20 questions. The data received from the outcomes of collecting data will be evaluated using univariate analysis, searching for the distribution of frequencies and averaged distributions of the variables studied, and using bivariate analysis via the Wilcoxon rank Test.Results: Women with children aged 1– 1.5 years. Of the 25 respondents in this category, 19 had a good level of knowledge, while 6 had a sufficient level of knowledge. After health education, the post-test findings showed that 24 participants had a good level of knowledge and 1 person had sufficient knowledge. Of the 30 mothers surveyed who have children aged 1.5– 2 years, the majority (20 respondents) showed a good level of knowledge. Of the responses received, only one had a low level of knowledge, while the other nine had a sufficient level of knowledge. After the health education, the post-test results showed that 26 participants showed a good level of knowledge. Of the 25 respondents who are mothers with children aged 2– 3 years, the majority (13 respondents) showed a good level of knowledge. Only one respondent had a low level of knowledge while the other 11 respondents had a sufficient level of knowledge. After health education, the post-test findings showed that 18 participants showed a good level of knowledge. Following healthcare learning, the post-test results revealed that 26 participants had a good level of understanding. The findings using the non-parametric in Wilcoxon Test, the significant values for respondents, particularly mothers with children ages 1– 1.5 a long time, 1.5– 2 years, and 2– 3 years, are 0.002, 0.000, and 0.000, respectively.Conclusion: In summary, before and after health education using leaflet media can increase mothers’ knowledge about stimulation of toddler growth and development in Gunung Tua the village, Subang Regency.Keywords: growth and development, leaflet, knowledge, stimulation, toddler